2023
DOI: 10.1021/acsphotonics.3c00821
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Strain Modulation of a Nanowire Quantum Dot Compatible with a Thin-Film Lithium Niobate Photonic Platform

Thomas Descamps,
Tanguy Schetelat,
Jun Gao
et al.

Abstract: The integration of indistinguishable single photon sources in photonic circuits is a major prerequisite for on-chip quantum applications. Among the various high-quality sources, nanowire quantum dots can be efficiently coupled to optical waveguides because of their preferred emission direction along their growth direction. However, local tuning of the emission properties remains challenging. In this work, we transfer a nanowire quantum dot onto a bulk lithium niobate substrate and show that its emission can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…In recent years, various techniques have been reported that achieved tuning of the QD emission but many are not suitable for NW-QDs. The QD-emission tuning techniques include stress-induced wavelength shift by piezoelectric actuators [10][11][12][13][14][15], laser-induced crystallization of the surrounding environment [16], thermal [17] and laser annealing [18], local electric Stark field [19], temperature-controlled tuning in a QD microlens [20], surface acoustic wave (SAW) modulation [21][22][23], laser-induced atomic intermixing in NW-QDs [24], stress induced by depositing dielectric material (SiO 2 ) on the nanowire surface [25], and external magnetic fields applied to NW-QDs [26]. However, these techniques often come with significant limitations and only few of them allow independent tuning of multiple quantum dots on the same chip.…”
Section: Articlementioning
confidence: 99%
“…In recent years, various techniques have been reported that achieved tuning of the QD emission but many are not suitable for NW-QDs. The QD-emission tuning techniques include stress-induced wavelength shift by piezoelectric actuators [10][11][12][13][14][15], laser-induced crystallization of the surrounding environment [16], thermal [17] and laser annealing [18], local electric Stark field [19], temperature-controlled tuning in a QD microlens [20], surface acoustic wave (SAW) modulation [21][22][23], laser-induced atomic intermixing in NW-QDs [24], stress induced by depositing dielectric material (SiO 2 ) on the nanowire surface [25], and external magnetic fields applied to NW-QDs [26]. However, these techniques often come with significant limitations and only few of them allow independent tuning of multiple quantum dots on the same chip.…”
Section: Articlementioning
confidence: 99%